Citrullinemia type I in Chinese children: Identification of two novel argininosuccinate synthetase gene mutations - Xiong, Mei; Chen, Mingwu (Frontiers in Pediatrics, 2022)
Abstract Background: In this study, we evaluated the clinical characteristics, prognosis, and gene mutations of five children with citrullinemia type I (CTLN1) diagnosed in our department and identified two novel ASS1 gene mutations. Methods: We examined the clinical characteristics, prognosis, and gene mutations of the five children through data collection, tandem mass spectrometry, and whole-exon sequencing. MutationTaster, regSNP-intron, and SWISS-MODEL were used for bioinformatic analysis to evaluate the two novel gene mutations. We analysed differences in blood ammonia and citrulline levels based on clinical phenotypes. Finally, we reviewed the medical literature describing Chinese children with CTLN1. Results: ASS1 C773+6T>G and c.848 delA as well as c.952_953 del insTT and c.133G>A have not been previously reported in the Human Gene Mutation Database. Using MutationTaster and regSNP-intron, we predicted that these mutations affected protein function. The 3D structure obtained using SWISS-MODEL supported this prediction. Through comparative analysis showed that the ammonia level of the neonatal type was markedly higher than that of other types, whereas citrulline levels did not differ between groups. Conclusion: We identified two novel mutations that cause disease. The blood ammonia level of neonatal form citrullinemia was markedly higher than that of other types. The genotype-phenotype association in Chinese patients remains unclear and should be further evaluated in genetic studies of larger sample sizes.